Policing major events : perspectives from around the world - Albrecht, James F. (2015)
"Whenever a major event requires police intervention, questions are raised about the nature of the police response. Could the police have prevented the conflict, been better prepared, reacted more quickly? Could they have acted more forcefully or brought the altercation under control more effectively? Based upon real case studies of events from all over the world, this volume explores the complex set of factors comprising the policing of major events. Topics covered include:Police procedures in Serbia in response to sporting events and violenceThe 2010 World Cup in South Africa as a model of best practice in governance structures, along with the region's struggles in routine policing initiativesSecurity operations at the 2010 Winter Olympic Games in Canada and the Summer Olympic and Paralympic Games in London in 2012Community involvement to curb terrorist insurgency in North Eastern NigeriaGovernmental response to Hurricane Katrina in Louisiana and TexasRevisions made to NYPD protocols following the September 11 attacksPolicing strategies for major events on Aboriginal and tribal lands across CanadaOther topics include the police/protestor relationship and low-profile versus high-profile policing strategies in crowd control, the growing strategy of private security in working with public police forces, and enhancing public safety in post-conflict regions. The concepts presented in Policing Major Events: Perspectives from Around the World will enable police departments to improve their readiness for policing major events across a diverse set of events and socio-political contexts. This book is a co-publication with the International Police Executive Symposium. "--
"Series Editor's Preface The International Police Executive Symposium (IPES) was founded in 1994 to address one major challenge i.e. the two worlds of research and practice remain disconnected even though cooperation between the two is growing. A major reason is that the two groups speak in different languages. The research is published in hard to access journals and presented in a manner that is difficult for some to comprehend. On the other hand police practitioners tend not to mix with researchers and remain secretive about their work. Consequently there is little dialogue between the two and almost no attempt to learn from one another. The global dialog among police researchers and practitioners is limited. True, the literature on the police is growing exponentially. But its impact upon day-to-day policing, however, is negligible. The aims and objectives of the IPES are to provide a forum to foster closer relationships among police researchers and practitioners on a global scale, to facilitate cross-cultural, international and interdisciplinary exchanges for the enrichment of the law enforcement profession, to encourage discussion, and to publish research on challenging and contemporary problems facing the policing profession. One of the most important activities of the IPES is the organization of an annual meeting under the auspices of a police agency or an educational institution. Now in its 17th year the annual meeting, a five- day initiative on specific issues relevant to the policing profession, brings together ministers of interior and justice, police commissioners and chiefs, members of academia representing world-renown institutions, and many more criminal justice elite from over 60 countries"--
"International Police Executive Symposium co-publication."
Keywords: Police; Violence -- Prevention; Security, International; LAW / Criminal Law / General; LAW / Forensic Science; POLITICAL SCIENCE / Political Freedom & Security / Terrorism